Amin Aiskrim / Badrul Amin Baharuddin - Badrul Amin, Baharuddin (2020)
Amin Aiskrim is a sole proprietorship business of ice cream shop that will bring the rich and high-quality taste of ice cream. It is located at No. 13 Parit 12 Sungai Panjang, 45300 Sungai Besar, Selangor. This place is chosen because the rental price in this area is cheaper compare to others and this area also nearby the school where suitable for our marketing target. Our marketing target mostly is primary school which students around 7-12 years old because kids loves ice cream more compare to the adults. Since it is located near the school, therefore is the most strategic areas for producing and marketing the products. The main product of our business is ice cream itself. There are many varieties of ice cream that we made and serve. For the ice cream, we used to serve the customer the flavours like Chocolate, Vanilla, Strawberry, Sweet Corn, Taro and Coconut. All our product basically are home-made ice cream that have been produced from many ingridient that have been imported from small farmer and cattle breeder nearby and also from Cameron Highland. Other than that, we decided to product our own merchandise that collab from the printing shop nearby. Basically we made an agreement with small scale printing shop. I want to help because we want to promote our local printing shop nearby also to others. A review of our competitor shows that we will be competing against other wellknown company which is Baskin Robins . These business focus on different target market, usage and well-planned marketing approaches. With my team consistent, high quality product, unique packaging and affordable price, my products have the edge in attracting consumer with help of promotion. The amount of loan I asked from Bank Islam is RM 50,000.00 and the amount of capital contributed by me is RM 20,000.00. The sales forecast for the first year is RM 867,130. In the future, we plan to market our product all over the Malaysia. We also plan to introduce this product internationally. Furthermore, I will also use media social, advertisement and create my product’s website to promote our business more. My team is includes marketing manager, financial management, administrative manager, operation manager and workers We want to operate the business according to mission which is to bring the high-quality products with the affordable price and to make our tasty Malaysia dessert being known around the world.